Qualitative Analysis of Some Antidiabetic Drugs by Spectroscopic Measurements - GUNASEKARAN, S.; NATARAJAN, R.K.; RENGANAYAKI, V. (Asian Journal of Chemistry, 2010)
Diabetes mellitus is an age-old disease plaguing mankind even today. Many oral antidiabetic drugs are available now-a-days to control the metabolic disorder in diabetes. The aim of the present work is to make a spectral investigation on some antidiabetic drugs, namely, glibenclamide and rosiglitazone maleate. The infrared, Raman and UV-Vis spectroscopic methods are employed for the qualitative analysis of these antidiabetic drugs. The different functional groups present in the compounds are identified and assigned satisfactorily using FTIR and FT Raman spectra. The UV-Vis spectral measurements carried out on the compounds identify the wavelength maxima. Using FTIR and UV-Vis spectral measurements, a comparison between the set of internal standards arrived at for the drugs stored in suitable storage conditions and exposed to environmental hazards is made.